Integrasi Seni Kreatif dalam Konseling dengan Pemanfaatan Seni Visual - Alhadi, Said; Saputra, Wahyu Nanda Eka (JURNAL FOKUS KONSELING, 2017)
Abstract:Â Innovation in the implementation of counseling services becomes a challenge for counselors. Currently, counselors are experiencing various obstacles to implement meaningful counseling services and have an effect on students. One effort to improve the quality of counseling services is with the use of creative arts, namely one visual art. There are five premises for the use of visual arts in counseling, namely: (1) describing the subconscious and helping the individual reveal secret conflicts that they did not reveal initially; (2) symbolize feelings in a unique, real, and powerful way; (3) to inspire and help counselees to achieve their personal growth; (4) assisting counselee especially children not feel threatened with counseling implementation; and (5) can easily be combined with other creative arts such as movement, creative writing, and imagery. With the utilization of visual arts is expected to improve the quality of counseling services meaningful and influential for students.Keywords: creative art, counseling, visual art